Pharmacological actions of a novel and selective dopamine D-3 receptor antagonist, KCH-1110 - Park, WK; Jeong, D; Yun, CW; Lee, S; Cho, H; Kim, GD; Koh, HY; Pae, AN; Cho, YS; Choi, KI; Jung, JY; Jung, SH; et al. (ACADEMIC PRESS LTD ELSEVIER SCIENCE LTD, 2003)
1-(2-Ethoxy-phenyl)-4-[3-(3-thiophen-2-yl-isoxazolin-5-yl)-propyl]-piperazine (KCH-1110), has a high affinity for human dopamine D-3 (hD(3)) receptor (K-i = 1.28 nM) with about 90-fold selectivity over the human dopamine D-2L (hD(2L)) receptor. Antipsychotic or antidopaminergic activity of KCH-1110 was investigated in the models for the positive symptoms of schizophrenia, apomorphine-induced climbing and cocaine-induced hyperlocomotion, in mice. Intraperitoneal (i.p.) or oral (p.o.) administration of KCH-1110 potently inhibited the apomorphine-induced cage climbing without any rotarod ataxia in mice. Cocaine-induced hyperactivity was also antagonised by KCH-1110. In addition, KCH-1110 attenuated the hypothermia induced by a selective dopamine D-3 agonist, 7-OH-DPAT in mice. KCH-1110 did not induce catalepsy in mice, but at much higher doses only a slight catalepsy response was shown. Although high doses of KCH-1110 significantly enhanced serum prolactin secretion in rats, low dose of KCH-1110 did not increase prolactin levels in rats. The present studies, therefore, suggest that KCH-1110 is a potent and relatively selective dopamine D-3 receptor antagonist with antipsychotic actions. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: WILD-TYPE MICE; COMPETITIVE ANTAGONIST; LOCOMOTOR-ACTIVITY; CLIMBING BEHAVIOR; PROLACTIN-RELEASE; MOTOR-ACTIVITY; HIGH-AFFINITY; IN-VIVO; RAT; LOCALIZATION